2021
DOI: 10.1002/cam4.4401
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a provincial symptom assessment program in reaching adolescents and young adults with cancer: A population‐based cohort study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…First, 21% of our cohort was not ESAS screened during a year of their cancer diagnosis. Past work has shown that these patients are more likely to live in low‐income urban neighborhoods or to have hematologic malignancies 26 . The symptom disparities we describe may thus be underestimated.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…First, 21% of our cohort was not ESAS screened during a year of their cancer diagnosis. Past work has shown that these patients are more likely to live in low‐income urban neighborhoods or to have hematologic malignancies 26 . The symptom disparities we describe may thus be underestimated.…”
Section: Discussionmentioning
confidence: 74%
“…AYA residing in the poorest urban neighborhoods were more likely to experience moderate and severe symptoms compared to those in the wealthiest areas. This is of particular concern as previous work found that these same AYA were also less likely to complete ESAS scores at all 26 . Similarly, AYA in Northern Ontario experienced more severe symptoms than those in urban Toronto.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Inpatients are not screened. Symptom scores are collected centrally in the Symptom Management Reporting Database …”
Section: Methodsmentioning
confidence: 99%
“…We created a retrospective population-based cohort of AYAs who were aged 15 to 29 years at primary cancer diagnosis between January 1, 2010, and June 30, 2018, as identified through the Ontario Cancer Registry . Populations who did not have ESAS access were excluded if they (1) received treatment in pediatric institutions, (2) did not require services at a RCC in the first year after diagnosis (eg, surgically resected thyroid cancer), or (3) were treated exclusively at non-RCCs.…”
Section: Methodsmentioning
confidence: 99%